An eye for an eye ; Gunless society ; Talking heads [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Features the death penalty imposition during the kidnap-killing of university students Castanos and Bernabe; proposal to have gunless society and interviews with a horce race caller, a sabong Kristo; stockmarket worker and Shoemart shoe lady.
An eye for an eye (16 min.) -- Gunless society (12 min.) -- Talking heads (13 min.)
VHS.
Keywords: Capital punishment -- Philippines; Firearms -- Philippines; Floor traders (Finance) -- Philippines -- Interviews; Gun control -- Philippines; Punishment -- Philippines